Avaliação da gestão em uma empresa de grande porte com base no Modelo de Excelência em Gestão (MEG) - Pontes, Daniel Fontenelle (2013)
Facing an increasingly competitive business, it is extremely important that companies pursue quality excellence. This paper aims to review the performance excellence through the application of the questionnaire Commitment to Excellence in a large company of the wind sector. Based on a literature review on the topic, a complete diagnosis of the company performance was made using the Management Excellence Model (GEM) of the National Quality Foundation (FNQ). The questionnaire asses eight topics : leadership, strategic planning, customers, community, human resources, information and knowledge, process management and business performance results. After the aplication of the questionnaire, the lowest scores were given to customers, business performance results and human resources respectively. Then, suggestions were made in order to the company to achieve excellence in quality management.